Temperature Screening for SARS‐CoV‐2 in Nursing Homes: Evidence from Two National Cohorts. Issue 12 (20th October 2020) - McConeghy, Kevin W.; White, Elizabeth; Panagiotou, Orestis A.; Santostefano, Christopher; Halladay, Christopher; Feifer, Richard A.; Blackman, Carolyn; Rudolph, James L.; Mor, Vince; Gravenstein, Stefan
Abstract : BACKGROUND/OBJECTIVES: Infection screening tools classically define fever as 38.0°C (100.4°F). Frail older adults may not mount the same febrile response to systemic infection as younger or healthier individuals. We evaluate temperature trends among nursing home (NH) residents undergoing diagnostic SARS‐CoV‐2 testing and describe the diagnostic accuracy of temperature measurements for predicting test‐confirmed SARS‐CoV‐2 infection. DESIGN: Retrospective cohort study evaluating diagnostic accuracy of pre–SARS‐CoV‐2 testing temperature changes. SETTING: Two separate NH cohorts tested diagnostically (e.g., for symptoms) for SARS‐CoV‐2. PARTICIPANTS Veterans residing in Veterans Affairs (VA) managed NHs and residents in a private national chain of community NHs. MEASUREMENTS: For both cohorts, we determined the sensitivity, specificity, and Youden's index with different temperature cutoffs for SARS‐CoV‐2 polymerase chain reaction results. RESULTS: The VA cohort consisted of 1, 301 residents in 134 facilities from March 1, 2020, to May 14, 2020, with 25% confirmed for SARS‐CoV‐2. The community cohort included 3, 368 residents spread across 282 facilities from February 18, 2020, to June 9, 2020, and 42% were confirmed for SARS‐CoV‐2. The VA cohort was younger, less White, and mostly male. A temperature testing threshold of 37.2°C has better sensitivity for SARS‐CoV‐2, 76% and 34% in the VA and community NH, respectively, versus 38.0°C with 43% and 12% sensitivity, respectively. CONCLUSION: A definition of 38.0°C for fever in NH screening tools should be lowered to improve predictive accuracy for SARS‐CoV‐2 infection. Stakeholders should carefully consider the impact of adopting lower testing thresholds on testing availability, cost, and burden on staff and residents. Temperatures alone have relatively low sensitivity/specificity, and we advocate any threshold be used as part of a screening tool, along with other signs and symptoms of infection.